Acute necrotizing encephalopathy in children with COVID-19: a retrospective study of 12 cases - Lin, Xia; Wang, Ying; Li, Xiaoying; Abdalla, Mohnad; Zhang, Fan; Dong, Chunhua; Lu, Weifeng; Liu, Xia; Zhang, Jian; Ma, Kang; Ma, Xiang; Jiang, Qin (Frontiers in Neurology, 2023)
Background Acute necrotizing encephalopathy (ANE) is a devastating neurologic condition that can arise following a variety of systemic infections, including influenza and SARS-Cov-2. The clinical features of COVID-19-associated ANE in pediatric patients based on multi-case data have not yet been described and remain obscure. We reviewed 12 pediatric patients to better describe the clinical features of ANE with COVID-19. Methods We retrospectively collected and summarized the clinical features of ANE in children with COVID-19. Clinical data were collected from 12 children, including their general status, clinical symptoms, laboratory tests, and neuroimaging features. Results Among the subjects, 10 were over 5 years old and they accounted for 83.33%. A large percentage of those affected (66.67%) were females. The major manifestations included fever (100%), impaired consciousness (100%), and convulsions (75%). We determined that increased interleukin (IL)-6 and IL-10, and tumor necrosis factor-α and interferon gamma were not predictive of severe ANE and mortality in children with COVID-19 in this study. All children presented with abnormal neuroimaging with multiple and symmetrically distributed lesions, involving the thalamus, basal ganglia, cerebellum, and brain hemispheres. Eight of the 12 children died, resulting in a mortality rate of 66.67%, and 75% of these children were females. Importantly, we found the timely administration of mannitol after an acute onset of convulsions or disturbance of consciousness may be decreased the high mortality induced by ANE children with COVID-19. Conclusion COVID-19 associated with ANE in children is characterized by sudden symptom onset, rapid disease progression, and high mortality.